Dispensing profile of non-steroidal anti-inflammatory drugs in a commercial pharmacy in a district of Belem-PA (Research, Society and Development, 2022)
This study aimed to evaluate the dispensing profile of the main oral non-steroidal anti-inflammatory drugs (NSAIDs) in a pharmacy in Belém-PA. Descriptive cross-sectional research of a quantitative and qualitative nature was carried out through the evaluation of the dispensing of NSAIDs for oral use, with and without medical prescription, in a commercial pharmacy, located in a district of Belém-PA from August to December 2021. 2,239 NSAIDs were dispensed, and the month with the highest number of sales occurred in December (46.58%). Paracetamol was the most dispensed drug (28.13%), followed by dipyrone (21.40%), nimesulide (19.35%) and ibuprofen (18.59%). It was found that 82% of sales were made without medical prescription, which indicates the indiscriminate use of this pharmacological class. Of these, paracetamol was the main NSAID dispensed without prescription (28.97%), followed by dipyrone (22.63%), nimesulide (18.41%), ibuprofen (17.60%) and diclofenac (12.40%). Despite the proven health risk, the indiscriminate use of NSAIDs still remains a routine practice by most people. The regular use of medicines requires constant assessment of health risks and attention in the prescription and dispensing of medicines is something relevant to public health.